Feinfühligkeit, Selbstverstrauen, Orientierung: Erfahrungen und Reflexionen zur elterlichen Kompetenz in der Spätmoderne aus der Sicht der Erziehungsberatung - Bushuven, Maria; Glar, Paul; Hoffmanns, Stefan (European Journal of Mental Health, 2015)
Empathy, Self-Confidence, Orientation: Parental Competence in Late Modernity from the Perspective of Educational Counselling in Germany: Experiences and Reflections: As an easily accessible service of youth and family protection, educational counselling has been available throughout Germany for over fifty years. Three social workers active in that field share on the basis of personal experience what they perceive as current pedagogical issues and problems stemming from a pluralistic, individualised environment that has lost its traditions. The authors encourage mothers and fathers not to resign to this open situation but to be present as parents and non-violently to confront their adolescent children with values, norms, their own expectations and desires. This can be most successful if parents can, from the beginning, develop a strong bond with their children even in difficult situations. The study is concluded with examples of preventive advising and counselling that enhances bonding.